Manajemen pelayanan perpustakaan perguruan tinggi islam - Iwan Sopwandin; Erni Haryanti; Dian Dian (STAI Ma'had Aly Al-Hikam Malang, 2020)
The study was to analyze the management of library services in uin mount djati bandung. The study USES a qualitative approach with a descriptive analysis method. Data collection techniques with participative observations, structured and unstructured interviews, and documentary studies. The analysis of the data in this study is done in three ways: data unitation, data categorization, and data interpretation. The search for library services management research found in mount dteal bandung shows that: 1) there are 11 types of service procedures; 2) service time on site for the update by 54 hours per week and online services can be obtained 24 hours nonstop via web and library applications; 3) services requiring an fee in the library, between which: a) the photoshop service, of rp500, rupiah/ page, b) the post - based member card service (lost) of rp100,000, d) 4) items for library services: a) physical products such as: a quick response code (QRC) visitors' lists, multi-purpose station (MPS), identification (rfid) of body technology (rfid), book drop machine; B) non - physical product: web based and application; 5) library facilities and infrastructure covered by the requirements for library accreditation, So the central library of uin msan bandung falls in the highest category (a); 6) the competence of library service officers according to competence standards based on Indonesian national performance standards, including general standards, content standards, and special standards.